The role of lithological layering and pore pressure on fluid‐induced microseismicity. Issue 2 (3rd February 2015) - Roche, V.; van der Baan, M.
Abstract The success of hydraulic fracturing treatments is often judged by the shape and size of the resulting microseismic cloud. However, it is challenging to predict the anticipated microseismic cloud prior to treatment. We use geomechanical modeling to predict the distribution of the microseismicity prior to the hydraulic fracture treatment. We analyze the likelihood of tensile and shear failure due to 1‐D variations in local stresses and rock strengths, induced by layering and pore pressure, for two field cases. The deviation in the local stresses from the regional stress field is induced by vertical variations in stiffness. This promotes failure of the stronger layers instead of the weaker ones since the stronger layers can become essentially load bearing. The simulations and field studies show that (1) microseismic events tend to locate preferentially where layers reach tensile failure due to fluid injection, and the number of events tends to decrease in layers that do not reach tensile failure; (2) shear initiation can occur in different layers from those failing in tension, thereby creating additional fluid migration paths; and (3) reactivation of preexisting fractures may occur due to fluid migration, even if their orientations are unfavorable. Numerical modeling is a significant aid in understanding the interplay of regional and local stresses and associated in situ failure due to variations in rock strength, pore pressure, and stiffnesses. In a wider perspective, it gives fundamental insights into the understanding of earthquakes and fault localization, the mechanisms of fracture development, and the role of fractures on fluid circulation and on the in situ stress field.